Prospective Single-Arm Trial of Endovascular Mechanical Debulking as Initial Therapy in Patients With Acute and Subacute Lower Limb Ischemia: One-Year Outcomes - Bulvas, Miroslav; Sommerová, Zuzana; Vaněk, Ivan; Weiss, Jiří (Journal of endovascular therapy, 2019)
PURPOSE: To report the results of a prospective, single-arm study to establish whether the initial treatment of acute or subacute limb ischemia (ALI and SLI, respectively) can be accomplished successfully using endovascular mechanical debulking of the target vessels to avoid the risks associated with thrombolysis and/or open surgery. MATERIALS AND METHODS: From April 2009 to April 2015, 316 consecutive patients (mean age 70.9±12 years; 184 men) with ALI (202, 63.9%) or SLI (114, 36.1%) were enrolled; the only exclusion criterion was irreversible ischemia. The ALI group included 146 (72.3%) participants with category IIb ischemia and 56 (27.7%) with category IIa. Critical limb ischemia was diagnosed in 74 (64.9%) of the 114 patients with SLI. Target occlusions of thrombotic (n=256) or embolic (n=60) origin were located in the femoropopliteal segment (n=231), prosthetic or venous femoropopliteal bypass grafts (n=75), and the aortoiliac segment (n=35). The mean occlusion length was 22.9±14.8 cm. RESULTS: The overall technical success (residual stenosis ≤30%) was 100% after debulking and adjunctive techniques (aspiration, dilation, stenting) at the level of the target lesions. No open surgical or thrombolytic modalities were necessary to bypass or recanalize the target vessels, and no death occurred in association with target occlusion therapy. Additional infrapopliteal interventions were performed in 195 (61.7%) patients (adjunctive thrombolysis in 29) to treat acute, subacute, and chronic lesions. Minor complications directly related to the debulking procedure occurred in 26 (8.2%) patients. Serious complications occurred in 11 (3.5%) patients, including hemorrhage in 8 (2.5%) patients (associated with infrapopliteal thrombolysis in 5). At 30 days, primary and secondary patency rates were 94.3% and 97.2%, respectively; mortality was 0.3% (1 fatal intracranial hemorrhage after adjunctive thrombolysis). Of 229 patients eligible for 1-year follow-up, amputation-free survival was estimated to be 87.4% in 199 patients with available data. CONCLUSION: In this all-comers study, mechanical debulking with the Rotarex alone or with adjunctive techniques is feasible as a primary therapy for occluded supratibial vessels in patients with ALI or SLI.
Keywords: dolní končetina; Limb Salvage; doba přežití bez progrese choroby; Peripheral Arterial Disease; acute limb ischemia; mužské pohlaví; Male; Czech Republic; senioři; senioři nad 80 let; Endovascular Procedures; thrombosis; debulking; Thrombectomy; Female; Humans; recidiva; trombektomie; lidé; embolism; záchrana končetiny; Prospective Studies; femoropopliteal segment; Time Factors; Middle Aged; ženské pohlaví; lidé středního věku; arterial occlusion; průchodnost cév; onemocnění periferních arterií; Acute Disease; Vascular Patency; Česká republika; mechanical thrombectomy; Amputation, Surgical; akutní nemoc; rizikové faktory; Ischemia; Young Adult; Progression-Free Survival; Aged, 80 and over; Thrombolytic Therapy; ischemie; Recurrence; prospektivní studie; mladý dospělý; trombolytická terapie; angioplasty; Lower Extremity; Risk Factors; dospělí; Adult; časové faktory; amputace; Aged; endovaskulární výkony